Accessing tacit knowledge: a street-level method. Issue 1 (2nd January 2021) - Bergheim, Berit
ABSTRACT: This article draws from a research project aimed at accessing tacit aspects of the practices of social workers engaged in outreach programmes for youth at risk. The article describes key features of the methods aimed at assisting these practitioners voice what the literature variously describes as tacit knowledge and practice wisdom. Following a presentation of the research design for the project and its relation to methods developed in earlier studies of the tacit dimensions of social work, the article describes how Gestalt therapeutic understandings influenced observations of face-to-face encounters between social workers and clients as well as follow-up discussions about these observations. After presenting illustrations of how these took place and summarising key elements of the methodology, the article then briefly discusses how these methods relate to social work practice research influenced by prhonetic social science. The article concludes by addressing the limitations and benefits shown by the project´s methods in helping social workers research practice as well as voice the tacit dimensions influencing how they think and act.